2021
DOI: 10.1093/hmg/ddab091
|View full text |Cite
|
Sign up to set email alerts
|

Selective serotonin reuptake inhibitor citalopram ameliorates cognitive decline and protects against amyloid beta-induced mitochondrial dynamics, biogenesis, autophagy, mitophagy and synaptic toxicities in a mouse model of Alzheimer’s disease

Abstract: In the current study, we investigated the protective role of citalopram against cognitive decline, impaired mitochondrial dynamics, defective mitochondrial biogenesis, defective autophagy, mitophagy, and synaptic dysfunction in APP transgenic mouse model of Alzheimer’s disease (ad). We treated 12-month-old wild-type (WT) and age-matched transgenic APP mice with citalopram for 2 months. Using Morris Water Maze and rotarod tests, quantitative RT-PCR, immunoblotting, biochemical methods and transmission electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 75 publications
0
21
0
Order By: Relevance
“…The long-term goal of our study was to understand molecular mechanisms involved in defective mitophagy in the progression and pathogenesis of AD. Emerging evidence from AD cell cultures, mouse and postmortem studies suggest that mitophagy is defective early on in the progression of disease [6, 39, 40, 7, 8, 26, 41, 18, 22, 29, 20, 24, 23]. Several studies provided compelling evidence that Aβ and P-Tau interacts with a large number of mitochondrial proteins such as Drp1, VDAC1 (voltage-dependent anion channel 1), CypD (cyclophilin D) and ABAD (amyloid beta-induced alcohol dehydrogenase), leading to induced free radical production, increased lipid peroxidation, and depletion of major mitophagy proteins, PINK1 and Parkin [6, 39, 40, 7, 8, 26, 41, 42, 22, 29, 20, 24, 23, 43, 44, 45].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The long-term goal of our study was to understand molecular mechanisms involved in defective mitophagy in the progression and pathogenesis of AD. Emerging evidence from AD cell cultures, mouse and postmortem studies suggest that mitophagy is defective early on in the progression of disease [6, 39, 40, 7, 8, 26, 41, 18, 22, 29, 20, 24, 23]. Several studies provided compelling evidence that Aβ and P-Tau interacts with a large number of mitochondrial proteins such as Drp1, VDAC1 (voltage-dependent anion channel 1), CypD (cyclophilin D) and ABAD (amyloid beta-induced alcohol dehydrogenase), leading to induced free radical production, increased lipid peroxidation, and depletion of major mitophagy proteins, PINK1 and Parkin [6, 39, 40, 7, 8, 26, 41, 42, 22, 29, 20, 24, 23, 43, 44, 45].…”
Section: Discussionmentioning
confidence: 99%
“…Our laboratory has been working to understand molecular events in mitochondria, aging, synapse and Aβ & P-Tau in AD over the last 2 decades; we have found that Aβ and P-Tau interacts with mitochondrial fission protein, Drp1, and mitochondrial outer membrane protein VDAC1, these interactions enhance GTPase Drp1 activity, increases mitochondrial fragmentation and most importantly depletes mitophagy proteins PINK1 and Parkin [26, 26, 41, 42, 22, 29, 20, 24, 23]. Based on these observations, we propose that a partial reduction of Drp1 reduces mitochondrial fragmentation, enhances biogenesis, mitophagy/autophagy, synaptic activity, dendritic spines, and improve cognitive functions in AD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mitochondrial abnormalities, including changes in mitochondrial DNA, mitochondrial gene expressions, mitochondrial ATP, mitochondrial enzymatic activities, mitochondria-induced increased free radicals, mitochondria-induced lipid peroxidation, reduced axonal transport, impaired biogenesis & dynamics and defective mitophagy are extensively reported in progression and pathogenesis of AD [4][5][6][7][8][9][10][11][12][13][14][15][16][17][26][27][28][29][30][31][32][33][34][35][36][37] . These changes are age-dependent, irrespective of type of AD -early-onset familial and late-onset sporadic.…”
Section: Introductionmentioning
confidence: 99%